Direct Drive System Applied to a Small Size League Robot - Simões, Henrique Barros; Tonidandel, Flavio (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
This paper compares a new transmission system and a new set of powertrains for robots in the Small Size League category of the RoboCup Soccer competition. The goal is to improve their speed and movement, leading to better performance and engine efficiency. Additionally, the study aims to optimize the robot's lower internal space to facilitate future improvements and integration of new technologies. The best types of powertrains in various arrangements, shapes, sizes, and the optimal motor/wheel system are studied, presenting a direct drive system that suits the league's evolution.